51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-279
|View full text |Cite
|
Sign up to set email alerts
|

Study on a Four-Cylinder Pulse Detonation Rocket Engine with a Coaxial High Frequency Rotary Valve

Abstract: Thrust measurement experiment was carried out using a four-cylinder pulse detonation rocket engine (PDRE) with a rotary valve. The PDRE uses three types of gases, oxidizer, fuel, and purge gas to generate detonation wave intermittently and produces thrust. We used a rotary valve attached coaxially to a motor for supplying these three gases intermittently. The mechanism of the rotary valve is very simple. It is built up with a top cover, a rotating disk, and a casing, and has advantage to enable high mass flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Their experimental results demonstrate that the frequency of the temperature and pressure is the same and their device is able to capture every pulse detonation quickly and precisely. Thrust measurement experiment was carried out by Morozumi et al [73] using a four-cylinder pulse detonation engine with rotary valve. Their experimental results achieved time averaged thrust of 258.5 N and specific impulse of 138.7 s. The detailed reactive detonation combustion flow features are experimentally investigated by Zitoun and Desbordes [74].…”
Section: Reviews On Experimental Analysismentioning
confidence: 99%
“…Their experimental results demonstrate that the frequency of the temperature and pressure is the same and their device is able to capture every pulse detonation quickly and precisely. Thrust measurement experiment was carried out by Morozumi et al [73] using a four-cylinder pulse detonation engine with rotary valve. Their experimental results achieved time averaged thrust of 258.5 N and specific impulse of 138.7 s. The detailed reactive detonation combustion flow features are experimentally investigated by Zitoun and Desbordes [74].…”
Section: Reviews On Experimental Analysismentioning
confidence: 99%
“…The results showed that the UAV with dual-tube pulse detonation engine could obtain higher flight speed. Morozumi et al 7,8 have achieved the time-averaged thrust of 258.5 N and specific impulse of 138.7 s by using a four-cylinder pulse detonation rocket engine with a rotary valve. Zhang et al 9 have developed an air-breathing PDE model with six tubes of 200 mm diameter and 1500 mm total length.…”
Section: Introductionmentioning
confidence: 99%